IMPLEMENTASI PERATURAN DAERAH KOTA PROBOLINGGO NOMOR 2 TAHUN 2024 DALAM PEMENUHAN HAK BERWIRAUSAHA BAGI PENYANDANG DISABILITAS DI KECAMATAN KANIGARAN KOTA PROBOLINGGO - Junaidi, Saviola Cinka Dihansa Junaidi; Supriyanto, Supriyanto; Yunus, Eko Yudianto (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2026)
This study aims to examine the implementation of Probolinggo City Regional Regulation Number 2 of 2024 concerning the Respect, Protection, and Fulfillment of the Rights of Persons with Disabilities, specifically regarding entrepreneurial rights in Kanigaran District. A descriptive qualitative approach with a single case study design was employed. Data were collected through in-depth interviews with four key informants, field observation, and documentary study. Data analysis used Miles and Huberman's interactive model, interpreted through Thomas B. Smith's policy implementation theory encompassing four variables: Idealized Policy, Target Groups, Implementing Organization, and Environmental Factors. Findings indicate that implementation has been underway but has not yet reached an optimal state. The policy possesses strong normative substance, yet socialization to target groups remains shallow and uneven. Entrepreneurial motivation among persons with disabilities is high, but constrained by limited capital, social stigma, transportation barriers, and insufficient post-training mentorship. The DKUP has conducted training and marketing facilitation programs, however capital support capacity and sustained mentorship remain critically limited. Environmental factors reveal potential through the KDK community and digital technology, while social stigma and transportation infrastructure continue to pose significant obstacles.